MiR-145-5p arrests the cell cycle by modulating SMAD5/cyclin D1 to inhibit gastric cancer progression - Wang, Li; Guo, Jianghong; Lv, Caixia; Kong, Luke; Cui, Jing; Wang, Zhongshuai; Guo, Yuanyuan; Jia, Ruirui; Guan, Tao; Yu, Baofeng; Li, Feng (Frontiers in Cell and Developmental Biology, 2025)
PurposeThis study aimed to explore the dysregulation of miR-145-5p in gastric cancer (GC) and its effects on the proliferation and cell cycle of GC cells, exploring the potential regulatory mechanism of miR-145-5p in GC.MethodsIn this study, the TCGA database combined with Microarray was used to detect differentially expressed microRNA (miRNA) in GC tissues and cells. Quantitative real-time (qRT)-PCR was used to further verify the expression of miR-145-5p in GC cells and the 41 pairs of GC tissues and adjacent tissues. A retrospective analysis was conducted on the correlation between miR-145-5p and the clinicopathological characteristics of patients with GC. The proliferation ability and cell cycle of AGS and MKN28 were detected by CCK-8, Edu and flow cytometry. The downstream target genes of miR-145-5p were screened by bioinformatics and further verified by the dual-luciferase reporter assay. Immunohistochemistry was used to detect the expression of SMAD5 in GC tissues. Western blot was used to detect cell cycle-related proteins that were regulated by siRNA SMAD5.ResultsThe expression of miR-145-5p was lower in GC tissues and cells compared with adjacent tissues and GES-1, and was related to the poor prognosis of patients with GC. Overexpression of miR-145-5p inhibited the proliferation of GC cells and blocked the cell cycle from G1 phase to S phase. MiR-145-5p targeted SMAD5 to inhibit the proliferation, and arrested the G1/S phase transition of GC cells. Mechanistically, SMAD5 siRNA significantly reduced CCND1 protein expression, Bioinformatics databases predicted that cyclin D1 was the transcription target gene of SMAD5. Moreover, the re-expression of cyclin D1 partially reversed the cell cycle arrest that was induced by SMAD5 depletion in GC cells.ConclusionTaken together, these findings reveal a novel role of the miR-145-5p/SMAD5/cyclin D1 axis in modulating cell cycle progression and cell proliferation in GC, which may provide a prognostic biomarker for GC treatment.